Implementation and evaluation of a Guide for the pharmacological management of admitted diabetic patients in the Internal Medicine Service - Luis Alberto Corona Martínez; Laydamí Rodríguez Amador; Ramón Ricardo Vélez Pérez; Sandra Borroto Lecuna; Caridad Hernández Abreus (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: Diabetes mellitus is a frequent cause of hospital admission. The authors have developed a Guide for the pharmacological therapeutic management of diabetics, which proposes a set of actions aimed at organizing medical care for diabetic patients in the Internal Medicine Service. Objective: to evaluate the process of implementing a Guide for the pharmacological therapeutic management of admitted diabetic patients with poor metabolic control or uncomplicated acute hyperglycemia status. Methods: a descriptive study, conducted at Dr. Gustavo Aldereguía Lima Hospital, in Cienfuegos, in May 2018. Compliance with the general actions proposed in the Guide was analyzed, as well as the introduction of the programmed subcutaneous insulin scheme; for this, several "process" and "results" indicators were used. Results: among the negative results indicators, the following were recorded: glycemic registration at the admission order (49%), patients´ stratification (29%), and stratification quality (60%), among others. Some with positive results were at the admission order to the decompensating factor (82%), adherence to the proposed behavior for each group (86%), use of the programmed subcutaneous insulin scheme (71%), consideration of the decompensation factor in therapeutic management (100%), and overall compliance with the scheme. The metabolic control was progressively achieved. Conclusion: the feasibility of applying programmed subcutaneous insulin therapy scheme proposed in the Guide, and its usefulness for the metabolic control of patients was confirmed.